Catalyst for synthesizing DMC (Dimethyl Carbonate) through oxidative carbonylation of methanol as well as preparation and application of catalyst

By using hydrophobic modification method in methanol oxidation carbonyl synthesis catalyst, the problem of poor catalyst stability is solved, and the effect of extending the service life of the catalyst and improving stability is achieved.

CN119456044APending Publication Date: 2025-02-18TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411595640.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

现有甲醇氧化羰基化合成碳酸二甲酯催化剂的稳定性较差,催化剂表面的Cu与副产物水反应导致Cu失活,且Cu颗粒在反应中长大降低反应活性。

Method used

The activated carbon support is used to self-reduce at high temperature after being supported by copper salt, and hydrophobic modification is carried out by silanizing reagent to form a hydrophobic copper-based catalyst, which prevents Cu from contacting with water and prevents Cu particles from agglomerating.

Benefits of technology

The hydrophobic layer formed by hydrophobic modification prevents the oxidation and agglomeration of the active component Cu, extends the service life of the catalyst and improves its stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119456044A_ABST
    Figure CN119456044A_ABST
Patent Text Reader

Abstract

The invention relates to a hydrophobic methanol oxidative carbonylation catalyst, preparation thereof and application of the hydrophobic methanol oxidative carbonylation catalyst in the field of DMC synthesis through methanol oxidative carbonylation. The hydrophobic copper-based catalyst suitable for the methanol oxidative carbonylation reaction is obtained by carrying copper salt on an activated carbon carrier, then carrying out high-temperature self-reduction and then modifying by utilizing a silanization reagent. The inner layer of the hydrophobic copper-based catalyst is an active component Cu, the outer layer of the hydrophobic copper-based catalyst is a hydrophobic alkyl group, and when the hydrophobic copper-based catalyst is applied to a methanol oxidative carbonylation reaction, the problem of catalyst deactivation caused by oxidation of the active component Cu by a byproduct H2O can be effectively solved, and the catalytic stability is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthesizing dimethyl carbonate by oxidative carbonylation of methanol, and in particular to a hydrophobic copper-based catalyst suitable for synthesizing dimethyl carbonate by oxidative carbonylation of methanol, and a preparation method and application thereof. Background Art

[0002] Dimethyl carbonate (DMC) is a non-toxic, environmentally friendly green chemical product. The DMC molecule contains multiple functional groups such as methyl, carbonyl, methoxy, and methoxycarbonyl. It has good reaction properties and can be used in methylation, carbonylation, methoxylation, and ester exchange reactions. It is known as the "new cornerstone" of organic synthesis in the 21st century.

[0003] The main methods for synthesizing DMC include phosgene method, transesterification method, urea method, methanol oxidation carbonylation method, etc. The phosgene method uses highly toxic phosgene and methanol as raw materials, has a long process flow, serious corrosion of equipment and pipelines, and pollutes the environment, and has been eliminated. The transesterification method uses propylene oxide (or ethylene oxide) to produce propylene carbonate (or ethylene carbonate), which is then reacted with methanol to produce DMC, but the selection and use conditions of the catalyst are relatively strict, and a large amount of by-products will be produced during the production process. The urea method uses urea and methanol as raw materials, and the reaction conditions are mild, but the product yield is low. The methanol oxidation carbonylation method uses methanol, O2, and CO as the main raw materials to synthesize DMC. The raw materials are cheap and easy to obtain, the reaction steps are simple, and the carbon atom utilization rate is high, which meets the requirements of clean production and green chemical industry.

[0004] The synthesis of DMC by oxidative carbonylation of methanol is carried out in an intermittent high-pressure slurry bed reactor. This technology uses highly active and inexpensive Cu as the active component, but the main problem is that the effective active component Cu on the catalyst surface easily reacts with the byproduct water produced in the reaction, causing Cu to undergo oxidation and deactivation. At the same time, the Cu particles in the catalyst grow during the reaction, reducing the reaction activity and resulting in poor stability of the Cu catalyst. Summary of the invention

[0005] In order to solve the above technical problems existing in the prior art, the present invention adopts the following technical solutions.

[0006] The first aspect of the present invention provides a methanol oxidation carbonylation synthesis DMC catalyst, which is obtained by the following preparation method: using an activated carbon carrier to load a copper salt and then self-reducing it at high temperature, then using a silanization agent to hydrophobically modify the high temperature self-reduction product, and vacuum drying the modified product to obtain a hydrophobic methanol oxidation carbonylation synthesis DMC catalyst with a metal Cu loading of 5%-30%.

[0007] The second aspect of the present invention is to provide a method for preparing a catalyst for synthesizing DMC by oxidative carbonylation of methanol, comprising the following steps:

[0008] S1. Pre-treat a certain amount of activated carbon with 0.5-5 mol / L nitric acid for 1-10 h, then place it in a 0.2-3 mol / L copper salt aqueous solution, ultrasonically treat it for 0.1-10 h, then vigorously stir it at room temperature for 3-12 h, then dry it at 60-120 ° C for 5-24 h, and then self-reduce the obtained dried sample at high temperature in an inert atmosphere for 2 to 10 h;

[0009] S2. Weigh a certain amount of the sample obtained in step S1 and disperse it in an organic solvent containing a silanization agent, perform hydrophobic modification for 2-5 hours under ultrasonic stirring, and vacuum dry the modified product to obtain a hydrophobic copper-based catalyst for oxidative carbonylation of methanol to synthesize DMC.

[0010] Preferably, the specific surface area of ​​the activated carbon carrier is 900-2000m 2 ·g –1 .

[0011] Preferably, the copper salt is one of copper nitrate hydrate, copper acetate or copper acetylacetonate, or a mixture of any two or more thereof.

[0012] Preferably, the silanization agent is any one of n-hexyltriethoxysilane and dodecyltriethoxysilane, or a mixture of two of them; and the organic solvent is any one of cyclohexane, n-hexane or toluene, or a mixture of two or more of them.

[0013] Preferably, in the solvent containing the silanization agent, the mass fraction of the silanization agent is 5% to 50%.

[0014] More preferably, the liquid-to-solid volume mass ratio of the sample to the organic solvent containing the silanization agent is 2:1 to 20:1.

[0015] In the above-mentioned preparation method, the temperature of the high-temperature self-reduction is 300-400°C.

[0016] In the aforementioned preparation method, the vacuum drying is drying at 50° C.-110° C. under vacuum conditions for 5-24 hours.

[0017] In addition, the third aspect of the present invention is to provide the use of the aforementioned methanol oxidation carbonylation synthesis DMC catalyst in a slurry bed reactor, and a preferred reaction process condition is: after the air in the slurry bed reactor is exhausted, it is pressurized to 2.0-5.0MPa with raw gas, and then the reaction is carried out under continuous stirring conditions, the reaction temperature is 100-140°C, and the reaction time is 0.5-4h; the raw gas is composed of CO and O2, wherein the partial pressure ratio of CO and O2 is 4:1-20:1.

[0018] Compared with the prior art, the hydrophobic methanol oxidative carbonylation catalyst for synthesizing DMC of the present invention has the following substantial characteristics and improvements:

[0019] The catalyst for synthesizing DMC by oxidative carbonylation of methanol provided by the present invention has a preparation process in which an activated carbon carrier is first treated with nitric acid so that the surface of the carbon material carrier has abundant oxygen-containing functional groups, which is conducive to the carbon material carrier carrying the active component reacting with the alkylating agent during the hydrophobic modification process, thereby grafting a large number of alkyl groups on the surface of the activated carbon, and then forming a hydrophobic layer on the surface of the catalyst, thereby obtaining a catalyst for synthesizing DMC by oxidative carbonylation of methanol with good hydrophobicity. When the catalyst is applied to the process of oxidative carbonylation of methanol, the hydrophobic layer on the surface of the catalyst forms a local hydrophobic microenvironment, which can prevent the contact of the active component Cu on the surface of the catalyst with the byproduct water, and avoid the oxidation of the active component Cu. At the same time, the presence of the hydrophobic layer enables the catalyst for synthesizing DMC by oxidative carbonylation of methanol of the present invention to form a confined area effect of the coating layer during the catalytic reaction, which can prevent the aggregation and growth of the active component Cu particles, and thus has the application effect of extending the service life of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is the water contact angle of the catalyst in Example 1 and Comparative Example 1.

[0021] Figure 2 The contact angle of the catalyst in Example 1 and Comparative Example 1 changes with time. DETAILED DESCRIPTION

[0022] The preparation method disclosed in this patent is further described below by specific examples, but the present invention is not limited to the following examples.

[0023] [Example 1]

[0024] First, 1.0 mol / L nitric acid was used to pretreat the activated carbon at 50°C for 3.0 h at a liquid-to-solid volume mass ratio of 3 mL:1 g. The pretreated activated carbon was washed with distilled water and dried for use. The pretreated activated carbon was added to a 0.5 mol / L Cu(NO3)2 aqueous solution, ultrasonically stirred for 10 min, and then stirred at room temperature for 6 h, and then placed in an oven at 80°C for 12 h, and then heated to 350°C at 2°C / min in an Ar atmosphere in a tubular furnace and maintained for 4 h for self-reduction treatment to obtain catalyst A1 with a Cu loading of 12 wt%.

[0025] Take 1 g of catalyst A1 and disperse it in a cyclohexane solution containing 15% by mass fraction of n-hexyltriethoxysilane (HTES) according to the liquid-solid volume mass ratio of the silanization agent to the catalyst of 5 mL:1 g. Ultrasonic stirring is carried out for 2 h, and then vacuum drying is carried out at 80 ° C to obtain a hydrophobic methanol oxidative carbonylation synthesis DMC catalyst, which is marked as Cu / CH.

[0026] The reaction performance of the catalyst for synthesizing DMC by oxidative carbonylation of methanol was evaluated in a slurry bed autoclave. The evaluation method is as follows: the air in the slurry bed reactor is exhausted and then pressurized to 2.0-5.0 MPa with feed gas, and then the reaction is carried out under continuous stirring conditions, the reaction temperature is 100-140°C, and the reaction time is 0.5-4 h; the feed gas is composed of CO and O2, wherein the partial pressure ratio of CO and O2 is 4:1-20:1. After the reaction, the catalyst is taken out from the liquid product and dried under vacuum conditions at 100°C for 6 h, and then the reaction is carried out 5 times under the same conditions, and 5% of fresh catalyst is replaced and supplemented to the reactor each time the evaluation is performed. The specific catalyst activity evaluation conditions are shown in Table 1, and the evaluation results are shown in Table 2.

[0027] [Example 2]

[0028] First, 2.5 mol / L nitric acid was used to pretreat the activated carbon at 60°C for 1.0 h at a liquid-to-solid volume mass ratio of 4 mL:1 g. The pretreated activated carbon was washed with distilled water and dried for use. The pretreated activated carbon was added to a 0.8 mol / L Cu(NO3)2 aqueous solution, ultrasonically stirred for 20 min, and then stirred for 10 h at room temperature, and then placed in an oven at 100°C for 12 h. The obtained dried sample was transferred to a tubular furnace and calcined at 400°C for 2 h at 8°C / min under N2 atmosphere for high-temperature self-reduction treatment to obtain catalyst A2 with a Cu loading of 16 wt%.

[0029] Weigh 1 g of catalyst A2 and disperse it in a cyclohexane solution containing 15% n-hexyltriethoxysilane (HTES) according to the liquid-solid mass ratio of the silanization agent to the catalyst of 10 mL:1 g. Ultrasonic treatment was performed for 3 h, and then vacuum dried at 90°C to obtain a hydrophobic methanol oxidative carbonylation synthesis DMC catalyst, which was marked as Cu / C-3H.

[0030] The reaction performance of the catalyst for synthesizing DMC by oxidative carbonylation of methanol was evaluated in a slurry bed autoclave in the same manner as in Example 1. In order to test the stability of the catalyst, the catalyst separated after the first reaction was dried at 60°C under vacuum for 8 hours, and 5 cycles of reaction were carried out under the same conditions, with 5% of fresh catalyst added to the reactor each time the evaluation was repeated. The specific catalyst activity evaluation conditions are shown in Table 1, and the evaluation results are shown in Table 2.

[0031] [Example 3]

[0032] First, 3.5 mol / L nitric acid was used to pretreat the activated carbon at 70°C for 2.0 h at a liquid-to-solid volume mass ratio of 5 mL:1 g. The pretreated activated carbon was washed with distilled water and dried for use. A 1.2 mol / L Cu(NO3)2 solution was prepared, and a certain amount of the aforementioned activated carbon carrier was added thereto. After ultrasonic treatment for 30 min, stirring was continued at room temperature for 8 h, and then placed in an oven and dried at 100°C for 12 h. The obtained dried sample was transferred to a tubular furnace and calcined at 350°C for 4 h at 10°C / min under a N2 atmosphere for high-temperature self-reduction treatment to obtain a catalyst A3 with a Cu loading of 20 wt%.

[0033] Weigh 1 g of catalyst A3 and disperse it in a cyclohexane solution containing 15% n-hexyltriethoxysilane (HTES) according to the liquid-solid mass ratio of the silanization agent to the catalyst of 15 mL:1 g. Ultrasonic treatment was performed for 3 h, and then vacuum dried at 60 ° C for 12 h to obtain a hydrophobic methanol oxidative carbonylation synthesis DMC catalyst, which was marked as Cu / C-5H.

[0034] The reaction performance of the catalyst for synthesizing DMC by oxidative carbonylation of methanol was evaluated in a slurry bed autoclave in the same manner as in Example 1. In order to test the stability of the hydrophobic copper-based catalyst, the catalyst separated after the first reaction was dried under vacuum at 60°C for 8 hours, and 5 cycles of reaction were carried out under the same conditions, with 5% of fresh catalyst added to the reactor each time the evaluation was repeated. The specific catalyst activity evaluation conditions are shown in Table 1, and the evaluation results are shown in Table 2.

[0035] [Example 4]

[0036] First, 4 mol / L nitric acid was used to pretreat the activated carbon at 80°C for 2.5h at a liquid-to-solid volume mass ratio of 6mL:1g. The treated activated carbon was washed with distilled water and dried for use. A 1.5 mol / L Cu(NO3)2 solution was prepared, and a certain amount of the aforementioned activated carbon carrier was added thereto. After ultrasonic treatment for 40min, stirring was continued at room temperature for 8h, and then placed in an oven and dried at 120°C for 12h. The obtained dried sample was transferred to a tubular furnace and calcined at 300°C for 6h at 5°C / min under N2 atmosphere for high-temperature self-reduction treatment to obtain catalyst A4 with a Cu loading of 24wt%.

[0037] Weigh 1 g of catalyst A4 and disperse it in a cyclohexane solution containing 15% dodecyltriethoxysilane (DTES) and n-hexyltriethoxysilane (HTES) according to the liquid-solid volume mass ratio of the silanization agent to the catalyst of 10 mL:1 g. Ultrasonic treatment was performed for 2 h, and then vacuum dried at 100 ° C for 4 h to obtain a hydrophobic methanol oxidative carbonylation synthesis DMC catalyst, which was marked as Cu / CD / H.

[0038] The reaction performance of the catalyst for synthesizing DMC by oxidative carbonylation of methanol was evaluated in a slurry bed autoclave in the same manner as in Example 1. In order to test the stability of the hydrophobic copper-based catalyst, the catalyst separated after the first reaction was dried under vacuum at 60°C for 8 hours, and 5 cycles of reaction were carried out under the same conditions, with 5% of fresh catalyst added to the reactor each time the evaluation was repeated. The specific catalyst activity evaluation conditions are shown in Table 1, and the evaluation results are shown in Table 2.

[0039] [Comparative Example 1]

[0040] The catalyst was prepared by referring to the catalyst preparation method of the present invention, but there was no hydrophobic modification step in the preparation process. The specific preparation method is that first, 1.0 mol / L nitric acid was used to pretreat the activated carbon at 50°C for 3.0 hours at a liquid-to-solid volume mass ratio of 3 mL: 1g, and the treated activated carbon was washed and dried for use. A 0.5 mol / L Cu(NO3)2 solution was prepared, and a certain amount of pretreated activated carbon carrier was added thereto so that the Cu loading was 12% (mass percentage), ultrasonicated for 10 minutes, stirred at room temperature for 6 hours, and then placed in an oven and dried at 80°C for 12 hours. The obtained dried sample was transferred to a tubular furnace and calcined at 350°C for 4 hours at 2°C / min under an Ar atmosphere for high-temperature self-reduction treatment. The solid product obtained after calcination is catalyst B1, marked as Cu / C.

[0041] The catalyst reaction performance evaluation and stability test methods are shown in Example 1. The specific activity evaluation conditions of the Cu / C catalyst in the methanol oxidative carbonylation reaction are shown in Appendix 1, and the evaluation results are shown in Table 2.

[0042] [Comparative Example 2]

[0043] The catalyst was prepared by referring to the catalyst preparation method of the present invention, except that the long-chain silane DTES was used for modification in the hydrophobic modification step of the preparation process. The specific preparation method is that first, 2.5 mol / L nitric acid is used to pre-treat the activated carbon at 60°C for 1.0h at a liquid-solid volume mass ratio of 4mL:1g, and the treated activated carbon is washed with distilled water and dried for use. A 0.8 mol / L Cu(NO3)2 solution is prepared, a certain amount of activated carbon carrier is added thereto, and after ultrasonic treatment for 20 minutes, stirring is continued at room temperature for 10 hours, and then placed in an oven and dried at 100°C for 12 hours. The obtained dried sample is transferred to a tubular furnace and calcined at 400°C for 2 hours at 8°C / min under N2 atmosphere for high-temperature self-reduction treatment to obtain a catalyst B2 with a Cu loading of 16wt%.

[0044] Weigh 1 g of the prepared catalyst B2 and disperse it in a cyclohexane solution containing 15% dodecyltriethoxysilane (DTES) according to the liquid-solid mass ratio of the silanization agent to the catalyst of 10 mL:1 g. Ultrasonic treatment was performed for 3 h, and then vacuum dried at 90°C to obtain a hydrophobic copper-based catalyst, which was labeled Cu / CD.

[0045] The catalyst reaction performance evaluation and stability test methods are shown in Example 1. The specific activity evaluation conditions of B2 catalyst in methanol oxidative carbonylation reaction are shown in Table 1, and the evaluation results are shown in Table 2.

[0046] Figure 1 , Figure 2 The contact angles of the catalysts in Example 1 and Comparative Example 1 and the curves of the contact angles changing with time are shown respectively. Figure 1 , Figure 2 It can be seen that hydrophobic modification of the supported copper-based catalyst by a silanization agent can effectively improve the hydrophobic type of the catalyst, and the contact angle of the catalyst is stably maintained at more than 110°, while the surface of the catalyst without hydrophobic modification is not hydrophobic. Analysis of the contact angle data in Example 1 and Comparative Example 1 shows that the stability of the modified catalyst is significantly better than that of the unmodified catalyst, indicating that the hydrophobic layer formed by the hydrophobic modification prevents the byproduct water in the reaction from poisoning the catalyst, and can effectively prevent water from contacting the active species in the catalyst, thereby improving the stability of the catalyst.

[0047] In order to verify the application performance of the catalyst prepared by the present invention. The catalysts provided in Examples 1 to 4, Comparative Examples 1 and 2 were tested for catalyst performance in a slurry bed reactor, with 1 to 10 g of hydrophobic copper-based catalyst added to 100 mL of methanol, and the liquid product after the reaction was analyzed for components using gas chromatography. The evaluation method and reaction conditions during the evaluation process are as follows:

[0048] After exhausting the air in the slurry bed reactor, the reactor is pressurized with raw gas so that the total pressure in the reactor is 2.0-5.0 MPa. The raw gas is composed of CO and O2, wherein the partial pressure ratio of CO and O2 is 4:1-20:1. The reaction process is carried out under continuous stirring conditions, the reaction temperature is 100-140°C, and the reaction time is 0.5-4h. At the same time, in order to test the stability of the catalyst, the catalyst separated after the first reaction is dried under vacuum conditions, and then used under the same conditions for 5 cycles of reaction, and 5% of fresh catalyst is replaced and supplemented to the reactor each time the evaluation is repeated.

[0049] The stability of the catalysts in the above examples and comparative examples was evaluated by the deactivation rate. The calculation formula for the deactivation rate is:

[0050] Where: C MeOH —The first methanol conversion rate in the initial stage of the reaction; C MeOH,5th —Methanol conversion rate at the 5th reaction.

[0051] Specific activity evaluation conditions and evaluation results are shown in Table 1 and Table 2, respectively.

[0052] Table 1

[0053]

[0054] Table 2

[0055]

[0056] As can be seen from Table 2, the deactivation rates of the hydrophobic copper-based catalysts Cu / CH, Cu / C-3H and Cu / C-5H prepared in Examples 1, 2 and 3 are all around 2%; in Comparative Example 2, the deactivation rate of the Cu / CD catalyst modified with long-chain silane DTES is as high as 29.8%, while the deactivation rate of the unmodified catalyst is as high as 29.2%. The above results show that short-chain hydrophobic modification can significantly improve the stability of the catalyst, but the overly long silanization modification will form a certain steric hindrance, hindering the reaction, and the anhydrous environment created by the short-chain silane modification can prevent the poisoning of the byproduct water to the active Cu species of the catalyst, and the hydrophobic effects of different amounts of silanization are different. Therefore, the hydrophobicity of the catalyst can be improved by selecting the appropriate chain length of the silanization agent and the amount used.

[0057] In addition, the presence of the hydrophobic layer enables the methanol oxidative carbonylation catalyst of the present invention to inhibit the interaction between the active component Cu and the byproduct water and inhibit the agglomeration and growth of Cu particles during the catalytic reaction, which helps to extend the service life of the catalyst. As shown in Table 2, the deactivation rate of the catalyst is significantly reduced, indicating that the catalyst prepared by the method of the present invention exhibits high catalytic stability in the cyclic reaction.

Claims

1. A catalyst for synthesizing DMC by oxidative carbonylation of methanol, characterized in that: The copper salt is loaded on an activated carbon carrier and then self-reduced at high temperature. The high temperature self-reduction product is then hydrophobically modified using a silanization agent. The modified product is vacuum dried to obtain a hydrophobic methanol oxidative carbonylation DMC catalyst with a metal Cu loading of 5% to 30%.

2. A method for preparing the catalyst for synthesizing DMC by oxidative carbonylation of methanol according to claim 1, comprising the following steps: S1. Pre-treat a certain amount of activated carbon with 0.5-5 mol / L nitric acid for 1-10 h, then place it in a 0.2-3 mol / L copper salt aqueous solution, ultrasonically treat it for 0.1-10 h, then vigorously stir it at room temperature for 3-12 h, then dry it at 60-120 ° C for 5-24 h, and then self-reduce the obtained dried sample at high temperature in an inert atmosphere for 2 to 10 h; S2. Weigh a certain amount of the sample obtained in step S1 and disperse it in an organic solvent containing a silanization agent, perform hydrophobic modification for 2-5 hours under ultrasonic stirring, and vacuum dry the modified product to obtain a hydrophobic copper-based catalyst for oxidative carbonylation of methanol to synthesize DMC.

3. The preparation method according to claim 1, characterized in that: The specific surface area of ​​the activated carbon carrier is 900-2000m 2 ·g –1 .

4. The preparation method according to claim 1, characterized in that: The copper salt is one of copper nitrate hydrate, copper acetate or copper acetylacetonate or a mixture of any two or more thereof.

5. The preparation method according to claim 1, characterized in that: The silanization agent is any one of n-hexyltriethoxysilane and dodecyltriethoxysilane or a mixture of two of them; the organic solvent is any one of cyclohexane, n-hexane or toluene or a mixture of two or more of them.

6. The preparation method according to claim 5, characterized in that: In the solvent containing the silanization agent, the mass fraction of the silanization agent is 5% to 50%.

7. The preparation method according to claim 6, characterized in that: The liquid-to-solid volume mass ratio of the sample to the organic solvent containing the silanization agent is 2:1 to 20:

1.

8. The preparation method according to any one of claims 2 to 7, characterized in that: The high-temperature self-reduction atmosphere is an inert atmosphere, and the self-reduction temperature is 300-400°C.

9. The preparation method according to any one of claims 2 to 7, characterized in that: The vacuum drying is drying at 50° C.-110° C. for 5-24 hours under vacuum conditions.

10. Use of the catalyst for synthesizing DMC by oxidative carbonylation of methanol according to claim 1 in a slurry bed reactor, characterized in that: After the air in the slurry bed reactor is exhausted, it is pressurized to 2.0-5.0 MPa with raw gas, and then reacted under continuous stirring conditions, the reaction temperature is 100-140°C, and the reaction time is 0.5-4h; the raw gas is composed of CO and O2, wherein the partial pressure ratio of CO and O2 is 4:1-20:1.